Contemporary procedural trends of Watchman percutaneous left atrial appendage occlusion in the United States. (11th November 2020) - Munir, Muhammad Bilal; Khan, Muhammad Zia; Darden, Douglas; Pasupula, Deepak K.; Balla, Sudarshan; Han, Frederick T.; Reeves, Ryan; Hsu, Jonathan C.
Abstract: Objective: To determine trends in real‐world utilization and in‐hospital adverse events from Watchman implantation since its approval by the Food and Drug Administration in 2015. Background: The risk of embolic stroke caused by atrial fibrillation is reduced by oral anticoagulants, but not all patients can tolerate long‐term anticoagulation. Left atrial appendage occlusion with the Watchman device has emerged as an alternative therapy. Methods: This was a retrospective cohort study utilizing data from National Inpatient Sample for calendar years 2015–2017. The outcomes assessed in this study were associated complications, in‐hospital mortality, and resource utilization trends after Watchman implantation. Trends analysis were performed using analysis of variance. Multivariable adjusted logistic regression analysis was performed to determine predictors of mortality. Results: A total of 17 700 patients underwent Watchman implantation during the study period. There was a significantly increased trend in the number of Watchman procedures performed over the study years (from 1195 in 2015 to 11 165 devices in 2017, p  < .01). A significant decline in the rate of complications (from 26.4% in 2015% to 7.9% in 2017, p  < .01) and inpatient mortality (from 1.3% in 2015% to 0.1% in 2017, p  < .01) were noted. Predictors of in‐hospital mortality included a higher CHA2 DS2 ‐VASc score (odds ratio [OR]: 2.61 per 1‐point increase, 95% confidence interval [CI]: 1.91–3.57), chronic blood loss anemia (OR: 3.63, 95% CI: 1.37–9.61) and coagulopathy (OR: 4.90, 95% CI: 2.32–10.35). Conclusion: In contemporary United States clinical practice, Watchman utilization has increased significantly since approval in 2015, while complications and in‐patient mortality have declined.